Standard Operating Procedures: A Safety Net for Pre-Analysis Plans. Issue 3 (15th July 2016) - Lin, Winston; Green, Donald P.
ABSTRACT: Across the social sciences, growing concerns about research transparency have led to calls for pre-analysis plans (PAPs) that specify in advance how researchers intend to analyze the data they are about to gather. PAPs promote transparency and credibility by helping readers distinguish between exploratory and confirmatory analyses. However, PAPs are time-consuming to write and may fail to anticipate contingencies that arise in the course of data collection. This article proposes the use of "standard operating procedures" (SOPs)—default practices to guide decisions when issues arise that were not anticipated in the PAP. We offer an example of an SOP that can be adapted by other researchers seeking a safety net to support their PAPs.